The Unbelievable Rightness of Being in Clinical Trials - Menikoff, Jerry (The Hastings Center report, 2013)
Much of what Ruth Faden and colleagues say squarely meshes with the ideas of the U.S. Department of Health and Human Services about reforming the system for protecting research subjects. Having said that, I want to turn to a very different part of the research universe, the elephant in the room, as it were: the world of interventional randomized clinical trials. Under the current regulatory system, these research subjects receive substantial protections. Most importantly, they are generally enrolled only after they give their informed consent. The rationale for this approach is that research subjects are denied the core ethical protection provided to patients: there is no requirement that everything done to them be in their best interests. Faden and colleagues appear to be proposing to eliminate this informed consent requirement for a significant range of such trials.